-6(x-1)=3(2-x)+4x

Simple and best practice solution for -6(x-1)=3(2-x)+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x-1)=3(2-x)+4x equation:


Simplifying
-6(x + -1) = 3(2 + -1x) + 4x

Reorder the terms:
-6(-1 + x) = 3(2 + -1x) + 4x
(-1 * -6 + x * -6) = 3(2 + -1x) + 4x
(6 + -6x) = 3(2 + -1x) + 4x
6 + -6x = (2 * 3 + -1x * 3) + 4x
6 + -6x = (6 + -3x) + 4x

Combine like terms: -3x + 4x = 1x
6 + -6x = 6 + 1x

Add '-6' to each side of the equation.
6 + -6 + -6x = 6 + -6 + 1x

Combine like terms: 6 + -6 = 0
0 + -6x = 6 + -6 + 1x
-6x = 6 + -6 + 1x

Combine like terms: 6 + -6 = 0
-6x = 0 + 1x
-6x = 1x

Solving
-6x = 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-6x + -1x = 1x + -1x

Combine like terms: -6x + -1x = -7x
-7x = 1x + -1x

Combine like terms: 1x + -1x = 0
-7x = 0

Divide each side by '-7'.
x = 0

Simplifying
x = 0

See similar equations:

| 5x+25=3x-15 | | (3x-2)(7x^2-x-6)= | | -6y=x+21 | | y+7=70 | | 6-7=5-6x | | -32+6x=10x+56 | | 3y-17=2x+2 | | 20=n^4 | | (-27y^9z^6)(2x^3y^3z^2)= | | -5+2[10b-2]=31 | | -1+6x=3x+32 | | 5x-9+5x=71 | | 3y-17=110 | | 2x-62=-32-x | | 4(w-3)=7+6w-19 | | 5x-70=t | | -6y-10y=-48 | | 6x+4=-8+4x | | 533=q^2+13q+23 | | 4-x-5x=58 | | -15+36=-10 | | 25=-5+5y | | -2x^2-4x=6 | | 9x+640x-5700=0 | | 6+4x=-2x+78 | | 7y=32-4y | | 1313=q^2+2213-60q | | -3x(x+5)=-3x+5 | | 3/4+2/5= | | 2x+32=32 | | 3x-8-7x=32 | | 10cos^2(30)= |

Equations solver categories